An Investigation into Professional Conflicts and Disputes in the Construction Sector - Owusu , Eric Edwin; Bonsu , Charles Akomea; Narh, Opata Christian; Oduro-Apeatu, K. (Recent Trends in Arts and Social Studies Vol. 1, 2023)
The purpose of this research is to determine the nature and causes of professional conflicts in the construction industry, their potential effects on the industry, and ways to reduce or eliminate them. Construction is crucial to the development process since it is frequently considered as an indicator of a country's socioeconomic progress. The nature of Ghana's construction industry creates an inherent conflict between the major stakeholders. One of the main goals of the construction industry in Ghana is to contribute to national socio- economic development by providing the buildings which are used in the production of all goods and services in the economy. The investigation begins with a review of previous works on the subject by various authors. Questionnaires were also distributed to various stakeholders in the construction industry, primarily consultants and contractors, with the goal of identifying construction disputes and conflicts in Ghana and developing strategies to prevent them. The collected data was quantitatively and qualitatively analyzed. According to the survey, conflicts exist on project sites, and among the causes are failure of clients to honor payments, unclear and incomplete descriptions of items in Bills of quantities, and delays in project completion, among others. The report offers various recommendations, such as hiring qualified employees and providing projects with appropriate funding, to lessen conflicts at project sites. The study comes to the conclusion that disputes actually occur and that resolving them incurs significant financial costs. Every aspect of the building process should consequently receive special attention.